Effects of gel lubricant on cervical cytology - Kittipat Charoenkwan (2018)
Objective: To determine whether the use of lubricating gel during vaginal speculum examination affected cytologic interpretation in the conventional Pap smear. Study Design: Two consecutive cervical smears were obtained from 1,334 patients undergoing Pap smear screening. The first smear (uncontaminated) was obtained using the routine collection technique. The second smear (gel-contaminated) was taken after applying a 1- to 1.5-cm ribbon of lubricating gel onto the external cervical os. Adequacy of Pap smear and discordance in diagnosis between the paired smears were examined. Results: The proportion of unsatisfactory smears was significantly higher in the gel-contaminated smears, 12.1% vs. 1.7% (p < 0.01). This difference was consistent across all reproductive groups. For patients who had smears satisfactoiy for cytologic evaluation, the discordance in cytologic diagnosis between the gel-contaminated and uncontaminated smears from the same patient was 0.3%. Conclusion: Lubricating gel contamination of the cervix can adversely affect adequacy and cytologic diagnosis in the conventional Pap smear. © The International Academy of Cytology.